MANAJEMEN LABA, TATA KELOLA PERUSAHAAN DAN PENGHINDARAN PAJAK - Setiorini, Hesti; Indrian, Rini; Midiastuty, Pratana Puspa (UNIB Press, 2017)
This study aims to analyze the effect of earnings management and corporate governance mechanisms gradually avoidance of taxes.The population of this study are property and real estate companies listed in Indonesia Stock Exchange 2013-2016. Sampling technique in this research using purposive sampling technique, with 128 data selected as sample. Analytical method used is multiple linear regression with SPSS program.The result of regression analysis proves that earnings management have an effect on tax avoidance. This study can not prove the effect of the proportion of independent board of commissioners, audit committee and managerial ownership on tax avoidance.